FLORENS’S RESISTANCE AGAINST SLAVERY IN TONI MORRISON’S A MERCY - DWI ARUM MARYATI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
FLORENS’S RESISTANCE AGAINST SLAVERY IN TONI MORRISON’S A MERCY Dwi Arum Maryati English Literature, Faculty of Languages and Arts, Surabaya State University dwiarummaryati@yahoo.com Drs. Much. Khoiri, M.Si English Department, Faculty of Languages and Arts, Surabaya State University much_choiri@yahoo.com Abstrak Studi ini berpusat pada Florens sebagai karakter utama dan sebagai orang kulit hitam dan pengalaman hidupnya dalam sistem perbudakan pada abad ketujuh belas di Virginia dan perlawanannya terhadap hal tersebut yang terungkap dalam novel A Mercy. Penelitian ini menggunakan kedua konsep, yaitu konsep perbudakan dan teori Marxis feminis oleh Karl Max. Selain itu, untuk perlawanan yang dilakukan oleh karakter utama, konsep pertahanan seperti istilah silent oleh Audre Lorde, divisi Lanser tentang feminisme dan konsep Engel tentang meniru kaum borjuis juga digunakan untuk melakukan analisis. Selain itu, latar belakang perbudakan di Virginia juga disampaikan untuk memberikan gambaran tentang perbudakan untuk menjawab alasan mengapa Florens ingin melawan sistem perbudakan. Data dalam bentuk kutipan, komentar, dan dialog dalam novel yang mengekspos perbudakan dan pengalaman hidup Florens dan perlawanannya. Analisis kehidupan perbudakan yang dialami oleh tokoh utama dalam novel ini menunjukkan bahwa ia telah hidup sebagai budak kulit hitam dan tidak memiliki hak untuk memiliki kehidupan yang lebih baik. Cara karakter utama mengungkapkan perasaannya tentang perbudakan melalui surat yang ditulis untuk majikannya dan sikap yang meniru kaum borjuis mencerminkan perlawanannya terhadap perbudakan. Kata Kunci: teori Marxist Feminist, perbudakan, orang kulit hitam, perlawanan. Abstract This study is centered on Florens as the main character and as a Negro and her life experiences of slavery in the seventeenth century in Virginia and her resistance against it in the novel A Mercy. The study uses both slavery concept and Marxist Feminist criticism by Karl Max. In addition, for the resistance that the main character does, the concept of resistance such as silent terms Audre Lorde, Lanser’s division of feminism and Engel’s concept about imitating bourgeoisie are also used to conduct the analysis. Moreover, slavery background in Virginia is also delivered to give a description about slavery to approach the reason why Florens wants to resist the slavery system. Data are in form of quotations, comments, and dialogues inside the novel that expose the slavery of Florens’s life experiences and her resistance. The analysis of slavery life experienced by the main character in the novel shows that she has lived as Negro slave and has no rights to have a better life. The way the main character expresses her feeling about slavery through the letter that she writes for her master and her attitude that imitating the bourgeoisie is reflecting the resistance against slavery. Keywords: Marxist Feminist criticism, slavery, Negro, resistance. INTRODUCTION Slavery is a relationship in which one person is controlled by violence through violence, the threat of violence, or psychological coercion, has lost free will and free movement, is exploited economically, and paid nothing beyond subsistence. (http://en.wikipedia.org/wiki/Slavery retrieved on October 20th, 2013). Slave means a person who is legally owned by someone else and has to work for them, while slavery means the activity of having slaves or the condition of being a slave. Historically, slaves were institutionally recognized by many societies. They recognized slaves merely as property but others saw them as dependents who eventually might be integrated into the families of slave owners. By the end of 17th century, there were many slavery system and freedom power of the different classes. In America Literary Thought Book reveals that indispensible to the rich sugar economy of the British West Indies, slavery at first was more a convenience than a necessity in the thirteen colonies. Slavery had been practiced in British North America from early colonial days. In 1619, twenty Africans were brought by a Dutch soldier who had seized them from a captured Spanish slave ship and sold to the English colony of Jamestown, Virginia as “indentured servants”. The Spanish usually baptized slaves in Africa before embarking them. As English law considered baptized Christians exempt from slavery, these Africans joined about 1,000 English indentured servants already in the colony. By Colonial America Period, in 1671 Governor Berkeley of Virginia reported 2.000 slaves in the colony as against 4.000 white servants, but after 1680 the Negro population began to grow enormously, and in 1715 had reached 23.000 in Virginia alone. (Horten and Edward, 1967: 376). The novel is A Mercy, and this novel has many sources in culture values and social status values. Both of them are combined into many action and many different events in each period at that time. Then, A Mercy by Toni Morrison depicts slavery which is happened in the end of 17th century. The author describes about the slavery situation, women slaves, the economic situation, and the resistance against slavery in Virginia to amuse reader in understanding this country. The issues are the slavery situation, women slaves, and resistance against slavery. These issues will be discussed more interesting and that the novel can reveal more complex than one perspective or a certain point in one character, or a setting of the study. Toni Morrison’s ninth novel, A Mercy, published in 2008. It is set in the 1690s, in the slave era, at a time when it was perilous to be without the “protection” of a man, independent women were still suspected of being witches and paternalistic relations between men and women were still the norm. In this novel, Morrison brings together representatives of all the major racial categories in the New World—African, Native American, Anglo and mulatto. A Mercy is set in the America of the 1680s, a dangerous time for everyone, male or female, slave or free. There’s Florens, Rebekka, Vaark’s wife; Lina, a dependable servant who is also Rebekka’s closest friend; Sorrow, an odd girl whose dreamy ways make her a poor slave; and Florens’ mother. As Morrison makes clear, all women in this world are at the mercy of the men in their lives; without them, these women are as good as lost. As one character notes, “To be female in this place is to be an open wound that cannot heal. Even if scars form, the festering is ever below.” By the slavery period in 1680’s, the slavery status can be treated and ruled. They did nothing, because of powerless people in a discrepancy, and there was a choice of freedom to get satisfaction. Florens, Lina, Sorrow, Willard, and Scully were the sacrificed people to be exploited in work area of slavery system by the master of household, and slave trades. As the novel progresses, other characters bring the New World to life, and each struggles to survive in the face of the wilderness that surrounds them. In addition to Florens, several other women add perspective to the novel, and each proves that no woman is truly free, regardless of color or station. In accordance of background study above, it can be simplify to discuss among two problems that emerge as significant concern toward this novel. How is slavery experienced by Florens in Toni Morrison’s A Mercy? How is Florens’s resistance against slavery in Toni Morrison’s A Mercy? This study will uses two concepts and one theory which are in line with the statement of the problems. The first problem is how slavery experienced by Florens depicted in A Mercy. To answer the first problem, this study uses the concept of slavery. Slavery is a system under which people are treated as property to be bought and sold, and are forced to work, (Brace, 2004: 163). There is also an additional slavery background in Virginia which is use to support the analysis. Then the second problem is how Florens’s resistance against slavery. This statement will apply the concept of resistance and Marxist feminist. This concept is developed by Karl Marx. It is use to analyze the bad treatment that Florens had as the oppressed low class woman from the brutality of her owner, her experience to confront the slavery and finally her resistance from slavery. RESEARCH METHOD Research methodology that used in this analysis here must be qualified as an applying in literary appreciation. The thesis is regarded as a descriptive-qualitative study and uses a library research. This study uses novel of Toni Morrison entitled A Mercy that published in 2008 as the data source of this study. The datas are in the form of direct and indirect speech of the characters, dialogues, epilogues and quotations which indicate and represent aspect of slavery and the way it is expressed. This thesis is using the library method in collecting the data. It does not use the statistic method. That is why it is not served in numbering or tables. Library research used an approach in analyzing this study. The kind of library research which is used here is intensive or closely reading to search quotations or phrases. It also used to analyze the literary elements both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the idea of analyzing. The analysis is done by the following steps: (1) Classification based on the statement of the problems. This classification is used to avoid the broad discussion. There are two classifications in this study. They are the depiction of slavery that experienced by Florens. (2) Describing the reason for being slave. Quotations classified the reason for being slave that was done by main character in the novel. (3) Describing the slavery that experienced by the main character. In this case, the quotations that showed and indicated the slavery experienced that was done by the main character. (4) Describing the main character’s resistance against slavery. In this case, the quotations that are showed how the resistance was done by the main character. (5) Drawing the conclusion based on the analysis which is in line with the problems. ANALYSIS The first section is about the description of Florens’s experiences being slave in Master Jacob house. Master Jacob brought Florens from Mr. D’Ortega to pay the whole amount he owes to Master Jacob. Sir saying he will take instead the woman and the girl, not the baby boy and the debt is gone. A minha mae begs no. Her baby is still at her breast. Take the girl, she says, my daughter, she says. Me. Me. Sir agrees and changes the balance due. (Morrison, 2008: 07) That quotation is revealed that Florens was a girl who had been purchased by the Master of Slave at America Slavery. Master Jacob brought Florens from Mr. D’Ortega to pay the whole amount he owes to Master Jacob. After losing the majority of his crew from bad management decisions, D'Ortega offers to give a slave to Jacob to settle their debt. Jacob initially refuses, but requests D'Ortega's favorite servant. Instead, the woman offers her daughter – Florens. The word “minha mae” here means a call for a mother in Portuguese language. She lived with her mother and her brother in Mr. D’Ortega’s house. Her mother had been slaved in Senhor house, who is a Parliament member in Maryland. In the beginning of the novel, Florens still call Jacob as “Senhor” and call Mr. D’Ortega as Sir. It means that at that time when the story took place, Florens still Mr. D’Ortega’s slave. In the other hand, if the slaveowner can sell or exchange their slave with a debt, the person who their change it must be a slave. Because if they change with a free person is set the law of human right, in that time (in 1690) slave usually can exchange with another materials for their Senhor. For the next psychical condition of Florens is she is known as the seven age years old when she firstly come to Master Jacob’s house, and she grow up to the sixteen years when Rebekka as her Mistress Jacob’s wife send her to find the blacksmith. Lina says from the state of my teeth I am maybe seven or eight when I am brought here. We boil wild plums for jam and cake eight times since then, so I must be sixteen. (Morrison, 2008: 05) When Florens firstly came to Master Jacob’s house she just seven years old, and she did not much understand how and why someone must say and faithful, because she is too young for understanding all things. Here she actually do not know her age exactly, perhaps she never given knowledge of her age from her another, that is why she write with word “or”. Here Florens just make statement “I am maybe seven or eight when I am brought here” it can be explained that she is seven ages when she bought to Master Jacob’s house. And when she retells her story, she just grows up as a girl in sixteen. Then, Florens also passed her day as a slave with her mother in the previous master’s house, as describe, Before this place I spend my days picking okra and sweeping tobacco sheds, my nights on the floor of the cookhouse with a minha mae. (Morrison, 2008: 05) This quotation above described Florens’s work in the previous master, Mr. D’Ortega. Her mother had been slaved in Senhor house, who is a Parliament member in Maryland. This condition makes Florens became a slave, because she was born from a slave. She has to fulfill her duties and help her mother. Because she was very young when she lived in Mr. D’Ortega, she got an easy job. She spend her days picking okra and sweeping tobacco sheds. In the night, she sleeps on the floor of the cookhouse with her mother. As a slave, she had no right to ask for a room to sleep, even she was in good health or sick. Moreover, Florens also got a similar treatment when she lives in her new owner, Master Jacob. As follows, In cold weather we put planks around our part of the cowshed and wrap our arms together under pelts. […] in summer if our hammocks are hit by mosquitoes Lina makes a cool place to sleep out of branches. (Morrison, 2008: 06) From the quotation above indicates that Florens treated not too different from the old master. In Master Jacob’s house, she sleeps in cowshed with Lina. They just use a planks to separated them with the cows and use the pelts to warm their hands and their body. And when summer comes, they sleep in hammocks that they bonded between two trees. If their hammocks are broken hit by mosquitoes, they build a bed from branches to sleep. Florens would do the slavery with a pleasure, and she wanted to a good treatment. Mistress Jacob had given her a training system to be a servant of household. And as a slave, she must obey all Mistress’s order. As reflected in her statement “It proves I am no body’s minion but my Mistress (Morrison, 2008: 111)”, it means that there was inseparable relationship between slave and their master because the slave owner paid for unlimited work. They have to fulfill their duty from their master at everytime and everywhere. Because the slave master has complete control over all aspects of the life of the slave, whether the slave is educated or provided medical treatment, what the slave eats and wears, and when the slave can ends their work at that day and sleeps. In America Slavery, there were many servants of the Master who had power and powerless in slavery system implied by the Master and Plantation Owners at that time. All the slaves had suffered on the slavery, because of them had no hope to change in the life chances of slavery. With the same position of them, they had worked on the time regularly and they had worked where the slavery rules was obeyed by the slaves. Therefore, this issue would appear a resistance against the slavery. Resistance occurs when some people feels something wrong against their will or unaccepted behaving. Also according to Marx, resistance occurs as class struggle for exploitation as the fundamental cause, due to the extent which increases the size of the exploitation of working class. In this case, the resistance in this novel has been done by a woman slave, named Florens. In contrast, she lived under a tremendous burden. As woman there are treated as inherently inferior to men and are mostly viewed as servants. She has the freedom of movement when she met the blacksmith. She had the thought of being married and changed her life as a free woman. Thus she has the freedom of choice. Moreover, this freedom of choice is complemented by her freedom of thought. The impetus of the entire novel is testament to Florens’s thought, as she narrates it to the reader. When a child I am never able to abide being barefoot and always beg for shoes, anybody’s shoes, even on the hottest days. (Morrison, 2008: 04) On this quotation revealed that Florens always want to life better. She was born as a nigger, but her desire to live like bourgeoisies lady is huge. She always wanted the best for her. But, born as a slave cause limitations to achieve her dreams. Even for shoes she has to beg for anybody. She tried to convince herself to make a change for her and the other slave. They may poor and worthless, but they want to live like a normal people whose not slave. She never let her foot being barefoot and hurt when she step her foot on the ground, just like bourgeoisie lady. This quotation can supports Marx and Engels’s prediction about woman and children in worker class will be a part of worker market, it is not impossible to them making reaction over the capitalism exploitation which increased not by doing revolution but slowly return woman and children into human source in order to imitate the bourgeoisie life style. Florens, she says, it’s 1690. Who else these days has the hands of a slave and the feet of a Portuguese lady? (Morrison, 2008: 04) From this quotation then can be said that her heart start to resist and says “enough” for the slavery thing. She decided that one day she will get her freedom but she is not taking some act directly. She waits till the right time show up and she will use that chance. As a starting, she changes her attitude and her perspective like a Portuguese lady which always live in glamorous. Moreover, Florens can read and write among three women in Master’s house. It can be seen in Lina’s statement about Florens, “Already Florens could read, write. Already she did not have to be told repeatedly how to complete the chore.” (Morrison, 2008: 61). That quotation revealed that Florens is a clever person, only herself who can read and write among three women. Master and Mistress also do not need to tell Florens many times to fulfill her work in the house. It means that Florens always one step ahead from others. This makes it easy for her to achieve her dream to be free and have a better life when she has a great thought. The highlight point on her resistance is she resists with non-violence actions as the author writing styles with full of simplicity. Until the time Master Jacob develops the pox while building his own grand home, and when close to death, he requests to be brought to the new house to die. After Jacob dies, Rebekka develops pox herself. It brings Florens to her passionate love for the unnamed man comes up again. Her obsession with the man illustrates her youth and inexperience in love. This man also happens to be Florens's lover, and she goes to him with hope in her heart for a new and different life. Lina sends her on a wagon to find the blacksmith since he was able to cure Sorrow of her pox previously. She thus begins her journey alone to find the man she loves with the medicine Rebekka needs. “I’m adoring you” Florens said “And a slave to that too” “You alone own me” (Morrison, 2008: 141) Indicates that her desire becomes stronger and she does not want to postpone it. This thinking is related to Lanser’s theory about the first level of feminism. “Feminine: The main female character in that literary looking about respect for her existence and tries to find a space in togetherness live with other social classes (man).” She belongs to this level due to her thought about marriage things. She wants to find a man who will pay the refund for her to Vaark’s family. Also her thinking also refers to find her existence while all the daylong she is considered as never existed. The blacksmith leaves almost immediately in order to reach Rebekka before the illness takes her life. The man who loved by Florens choose his child rather than being married with Florens. While Florens is overjoyed to be with the blacksmith again, she realizes that he may not feel the same way. He has adopted a young boy, and Florens is worried because the blacksmith acts as if the boy is his future. Not Florens. He tells her, "Own yourself, woman, and leave us be". Florens is in shock over her lost love and once again feels the pain of abandonment she first experienced when her mother urged Jacob to take her. It means her internal conflict appears again and she already thinks about getting her freedom. Her desire to get free is close enough and makes her thinks to leave Vaark’s family as soon as she can. Since her way to get freedom from being married with the blacksmith is failed. Thus, Mistress is now paying Willard and Scully to help out on the farm, while Mistress herself "beats Sorrow, has Lina's hammock taken down, and advertises the sale of Florens" (Morrison, 2008: 155). This quotation revealed that as Florens’s owner, Mistress uses her power and authority to anything to her slave, including sell her to the new owner. Scully allows these things to happen without remarking on them because he needs the money Rebekka is paying him in order to one day be free. As Rebekka considers selling Florens and giving Sorrow, the girl who has an imaginary friend and is too naive to understand her pregnancies away, Sorrow wants to escape. But, Florens wants to finish her story to the blacksmith and Mistress. Afterwards, she runs back to the Vaark farm. Florens is writing her story on the floor and walls of the big house Jacob insisted upon constructing. “You won’t read my telling. You read the world but not the letters of talk.” (Morrison, 2008: 160). She writes both in hopes that the blacksmith will one day read her account as well as a means to catharsis, to free herself from the pain of her multiple abandonments. Florens laments the changes Rebekka has undergone as a result of her new religious piety and the cruelty she has enacted upon the slaves, as described, Downstairs behind the door in the room where Sir dies. Mistress slaps her face. Many times. […..] Her churchgoing alters her but I don’t believe they tell her to behave that way. (Morrison, 2008: 159) Florens' reiterates the blacksmith's conviction about intellectual slavery and writes "that it is the withering inside that enslaves and open the door for what is wild" (Morrison, 2008: 187). Even though the process of writing is painful, "My arms ache but I have need to tell you this" (Morrison, 2008: 188), it is necessary to do so in order for Florens to be free, as follows, I am become wilderness but I am also Florens. In full. Unforgiven. Unforgiving. No ruth, my love. None. Hear me? Slave. Free. I last. (Morrison, 2008: 161) From the quotation above indicates that she begins saying her opinion, her willing to get free through the letter. Like Audre Lorde’s statement about silence transformed into an action, Florens statement is considered to be her action form and also as David B. Loughram stated about resistance types: speech and action. Actually she really in a crisis situation because she can get caught and killed by stating statements that she wants to be free by herself not by her master. Her action actually has a big risk, remembering the rule of slavery is they do not have any rights to speak or against their owner as the person who has the power in exploiting and controlling them. Declaring that she is free by herself clarified that she is truly freed from Mistress Jacob’s slavery. This quotation strongly supports Florens to classify as the second level feminist according to Lanser. Therefore, she belongs to the second level feminism because she already takes an action by brave stating her freedom and took a defense from the physical abused from her owner. CONCLUSION In this chapter, the conclusion of the study of Florens’s Resistance Against Slavery in Toni Morrison’s A Mercy is stated. Based on the analysis of the study there are two conclusions which related with statements of the problems drawn: the depiction of Florens’s experienced in Slavery in Toni Morrison’s A Mercy, and the resistance against slavery in the novel. First, the study shows the events were depicted the slavery that experienced by the slave who served their master in the novel. There is a main character who is Florens and some other supporting character who had been slave. Florens is African Black Slave Girl, Lina is Native American Slave, Sorrow is a mixed – blood girl and she was an unpaid slave, Willard and Scully are indentured servants from Europe. Therefore, they get different responsibility and different treatment of Master Jacob’s determination in the farm house, and companies. Toni Morrison shows up a certain illustration of a slavery background and how Florens was working and getting a different treatment and a different benefit that lead to resistance against slavery. Florens came from family in a poor line, and she was taken by Master Jacob Vaark, and she had helped to the Jacob’s family as a household. At the last period, she was a Negrita Girl. Florens has worked to the tobaccos company, and Master provided to her in living, and he also gave a good care for her condition. After Master died, she did not find a protection from Mistress. She wanted to escape from a Big House when Mistress wants to sell Florens again for the second time. Same as Florens, Sorrow wanted to escape from a Big House after Master died, because Mistress Jacob gave displeasure treatment on her works in a garden and sewing training. She also treated by Mistress Jacob with displeasure when she took a care for her baby intensively. Mistress Jacob did not like Sorrow’s baby while she had lost of her baby. Second, the main character, Florens, resists the system of slavery by doing resistance to her owners, Vaark’s family. Her resistance can be seen from her action and also her speech through letter that she written in Big House as the types like David B. Loughram stated. Her resistance also categorized as non-violence resistance because she does not do anything harmful when she resists them. It also the way to fulfill her material needs; freedom (as in historical materialism discussed). She also categorized into second level feminism as Lanser observed; she declare her freedom by herself is categorized into the second level. Because she already brave to speak up and take some action to realized her dream. Moreover, she considers as young sophisticated woman because all education and knowledge that she got when she was working as slave in Vaark’s family. This case also represents Engels’s theory in his works which stated about “Imitating bourgeoisie”. Florens in here is the represent from Engels’s theory. She imitates the bourgeois life style. She speaks like them, her style like them, and also wants to marry and living like them. REFERENCE Brace, Laura. 2004. “Slaveries and Property: Freedom and Belonging”. The politics of property: labour, freedom, and belonging. Edinburgh: University Press. Engels, Friedrich. 1884. The Origins of the Family, Private Property and the State. Atlanta: Pathfinder Press. Horton, Rod W and Herbet Edward. 1967. Background of American Literary Thought. New York: APPLETON-CENTURY-CROFTS Division of Meredith Corporation. Loughran, David B. 1998. Rebellion. Scotland: Stewarton Bible School Press. Marx, Karl. 1887. Das Capital. Moscow: Progress Publishers. Morrison, Toni. 2008. A Mercy. New York: A Division of Random House, Inc. Olson, Loster C. 1997. “On the Margins of Rhetoric: Audre Lorde Transforming Silence into Language and Action”. Quarterly Journal of Speech 83. pp. 49-70. Internet Source: (http://en.wikipedia.org/wiki/History_of_slavery_in_Virginia) retrieved on October 20th, 2013. (http://en.wikipedia.org/wiki/Slavery) retrieved on October 20th, 2013.